1997
DOI: 10.1002/(sici)1097-0215(19971021)74:5<502::aid-ijc4>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of p53 and vascular endothelial growth factor expression in colorectal carcinoma for determination of tumor vascularity and liver metastasis

Abstract: Recent studies have demonstrated that the p53 tumor suppressor gene plays an important role in controlling tumor angiogenesis. We examined the expression of p53 and vascular endothelial growth factor (VEGF), a well‐characterized angiogenic inducer, together with microvessel density to investigate the role of p53 in the regulation of angiogenesis and its clinical significance in human colorectal carcinoma. Surgically resected specimens of 163 colorectal carcinomas were studied by immunohistochemical staining fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 17 publications
7
59
4
Order By: Relevance
“…In established cancers, p53 inactivation is commonly associated with intracellular p53 protein accumulation (Hall and Lane, 1994). The present study has shown p53 accumulation in 59% of colorectal tumours, in accord with previous findings (Kang et al, 1997;Ahnen et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In established cancers, p53 inactivation is commonly associated with intracellular p53 protein accumulation (Hall and Lane, 1994). The present study has shown p53 accumulation in 59% of colorectal tumours, in accord with previous findings (Kang et al, 1997;Ahnen et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Functional inactivation of p53 promotes genomic instability (Bischoff et al, 1990) and is commonly, though not universally, associated with intracellular p53 protein accumulation (Hall and Lane, 1994;Save et al, 1998). p53 accumulation is detectable in many colorectal cancers (Purdie et al, 1991;Scott et al, 1991), with 40-60% having immunologically detectable levels (Kang et al, 1997;Ahnen et al, 1998). However, effects on growth homeostasis are unclear.…”
mentioning
confidence: 99%
“…5,[43][44][45][46][47] Some studies have indicated that VEGF expression is an independent prognostic factor in predicting patient prognosis, 5,[43][44][45] while others have reported no such association. 46 Chung et al 47 also showed that VEGF expression was significantly associated with prognosis and hematogenous spread in colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization sustained by VEGF up-regulation is necessary for tumour nourishment and it is a potential route for haematogenous spread and metastasis. Previous data contribute to support this hypothesis; high VEGF protein expression or mRNA levels correlated with the M1 stage and liver metastases from colorectal carcinomas (Kang et al, 1997;Tokunaga et al, 1998;Lee et al, 2000).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 82%